Cost estimation methods for internet infrastructure deployment in Rural Sarawak: a review - Abel Yu Hao, Chai; Chean Hung, Lai; Hieng Tiong, Su; Yi Lung, Then; Fei Siang, Tay; Patrick Hui Then, Hang; Natalie Chen Yi, Lim (Institute of Advanced Engineering and Science, 2020)
In rural Sarawak, the internet accessibility is low due to unreliable power grids to support telecommunication network and large geographical area. The risk for network infrastructure implementation is high for internet service provider (ISP), thus more practical and accurate cost estimation methods should be used. This paper reviews different types of cost estimation methods and the accuracy and feasibility of each methods are discussed and compared for network infrastructure implementation in rural Sarawak. The unique characteristics of rural Sarawak are considered in this work, including the topography, development of rural areas and acceptance of new technologies. Different cost estimation methods are identified for different senarios and availability of data.